Operational performance of a Plasmodium falciparum ultrasensitive rapid diagnostic test for the detection of asymptomatic infections in Eastern Myanmar - Landier, J; Haohankhunnatham, W; Das, S; Konghahong, K; Christensen, P; Raksuansak, J; Phattharakokoedbun, P; Kajeechiwa, L; Thwin, M; Jang, I; Imwong, M; Wiladphaingern, J; et al. (American Society for Microbiology, 2018)
Context In the Greater Mekong Subregion, malaria elimination strategies target all Plasmodium falciparum parasites, including those carried asymptomatically. Over 70% of asymptomatic carriers are undetectable by current rapid diagnostic tests (RDT) or microscopy. An HRP2-based ultrasensitive RDT (uRDT) developed to improve the detection of low density infections was evaluated during prevalence surveys within a malaria elimination program in a low transmission area of Eastern Myanmar. Methods Surveys were conducted to identify high prevalence villages. A 2mL venous blood sample was collected from asymptomatic adult volunteers and transported to the laboratory. Plasmodium parasites were detected by RDT, uRDT, microscopy, ultrasensitive qPCR (uPCR) and ELISA. The sensitivity, specificity, predictive positive and negative values were calculated compared to uPCR and ELISA. Parasite and antigen concentrations detected by each test were defined using uPCR and ELISA. Results 1509 samples, including 208 P. falciparum positive were analysed with all tests. The uRDT had a two-fold higher sensitivity compared to the RDT, 51.4% versus 25.2%, with minor specificity loss, 99.5% vs 99.9% against the combined reference (uPCR+ELISA). The geometric mean parasitemia detected by uRDT in P. falciparum monospecific infections was 3,019 parasites per mL (95%CI=1,790-5,094; n=79), compared to 11,352 (95%CI=5,643-22,837; n=38) by RDT. The uRDT and RDT sensitivity dropped to 34.6% and 15.1% respectively for the matched tests performed in the field. Conclusion The uRDT performed consistently better than RDT and microscopy at low parasitemias. It shows promising characteristics for the identification of high prevalence communities and warrants further evaluation in mass screening and treatment interventions.